El Recorrido: reinterpretación de la arquitectura isleña en centro turístico eco-cultural en la Isla de Providencia. Colombia. (2022)
The urban landscapes have important effects when rebuilding city in extreme situations, the presence or absence of water, the conditions of the vegetation, the furniture influences how the city lives in case of emergency. The planning of the territory in these cases goes beyond rebuilding. Moreover, it is a concern for settlements in an integral way, due to the identification of some physical, economic, social and environmental values. In the stage of the case of the island of Providencia, which has been exposed to a strong hurricane a few months ago, and that this brought consequences not only in the physical infrastructure of the island but also in its economy, which is mainly governed by tourism. The thesis proposes to reinterpret and apply the characteristics of traditional island architecture in an urban and architectural model of eco-cultural tourism, with the ultimate goal of reactivating the economy of the island of Providencia. Colombia